EPIDEMIOLOGY AND IMPACT OF HUMAN PAPILLOMAVIRUS ON PREGNANT WOMEN'S HEALTH - Amonova Z. D.; Kattakhodzhaeva M. Kh. (Modern American Journals, 2025)
Human papillomavirus (HPV) is one of the most common sexually transmitted infections and causes a number of diseases, including cervical cancer. This study examines the peculiarities of HPV epidemiology among pregnant women, the impact of the infection on reproductive health, and possible complications for mother and child. Geographical differences in the spread of the virus and the factors influencing the development of the disease in this group of women are also discussed. The purpose of the study is to analyze the epidemiological situation, as well as the impact of HPV on pregnancy outcomes and newborn health.
Keywords: HPV, pregnancy, cervical intraepithelial neoplasia, prevalence, geographic differences, pregnancy complications, reproductive health.